Synthesis, Crystal Structure and Spectral Studies of M(hsm)(2)(sac)(2) Complexes (M=Cu, Ni and Cd) - Kastas, Gokhan; Pasaoglu, Humeyra; Bulut, Iclal (Int Union Crystallography, 2006)
…
Keywords: Histamine; Saccharin; Metal Complex